Assessment of thyroid function among children with epilepsy receiving anticonvulsant monotherapy: a hospital based prospective study - Rahman, Ushuf; Islam, Munshi Safikul (International Journal of Contemporary Pediatrics, 2020)
Background: Data on influence of antiepileptic drugs (AED) on thyroid profile in children is limited and is still controversial. This study aimed to investigate the effects of valproate, levetiracetam, phenobarbitone and oxcarbazepine monotherapy on thyroid function in children after one year of therapy. Method: A total of 106 children (39 girls and 67 boys) with new onset and controlled epilepsy treated with valproate (n=52), phenobarbitone (n=12), oxcarbazepine (n=14) and levetiracetam (n=28) were enrolled in the study. Serum thyroxine (T4, T3) and thyroid-stimulating hormone (TSH) level were measured before and at one year of therapy. Results: At baseline average T4, T3 and TSH concentrations were not different between the drug groups. Except levetiracetam all antiepileptics increased TSH after one year of therapy and there was significant difference in TSH increment in valproate treated patients compared to other anticonvulsants. All anti-epileptics except levetiracetam was found to decrease T4 and T3 after one year of therapy but there was no significant difference among the groups, unlike TSH. Sodium valproate was the most frequently used antiepileptic drug. None of children had any symptoms of hypothyroidism, only 3% had signs of hypothyroidism which included goitre on examination. Out of various seizure disorders generalised tonic clonic type was most common (47.5%) followed by atypical febrile seizure (23%). Conclusions: All antiepileptic drugs studied except levetiracetam had varying degrees of deleterious effects on thyroid function.